Determining motivation to engage in safe food handling behaviour - Mullan, Barbara; Allom, Vanessa; Sainsbury, Kirby; Monds, L. (Elsevier Ltd, 2016)
Purpose: To apply the protection motivation theory to safe food handling in order to determine the efficacy of this model for four food handling behaviours: cooking food properly, reducing cross-contamination, keeping food at the correct temperature and avoiding unsafe foods. Design: A cross-sectional approach was taken where all protection motivation variables: perceived severity, perceived vulnerability, self-efficacy, response efficacy, and protection motivation, were measured at a single time point. Findings: Data from 206 participants revealed that the model accounted for between 40 and 48% of the variance in motivation to perform each of the four safe food handling behaviours. The relationship between self-efficacy and protection motivation was revealed to be the most consistent across the four behaviours. Implications: While a good predictor of motivation, it is suggested that protection motivation theory is not superior to other previously applied models, and perhaps a model that focuses on self-efficacy would offer the most parsimonious explanation of safe food handling behaviour, and indicate the most effective targets for behaviour change interventions. Originality: This is the first study to apply and determine the efficacy of protection motivation theory in the context of food safety.